Examining institutional entrepreneurship at early moments: the case of mobile health in England and Finland - Nyberg, R (2014)
If you have an idea about applying a proven technology to improve the processes in a new area of society, what does it take to implement it in a way that it has wide impact and endures? This is a relevant question particularly now, at the dawn of the age of 'big data', as information and communication technologies are adopted in many areas to harness the ability to collect, retrieve and analyse large amounts of information, and be made available at the level of individual users. Extraordinarily powerful devices developed in recent years offer much promise, but as many examples, such as Betamax, WAP-technology, HD DVD and netbooks, show that even potent technologies may fail to gain predominance and survive. The concept of institutional entrepreneurship is a useful framework to analyse these complex issues as it embodies a comprehensive analytical perspective, combining attention to the institutional environment as well as to the efforts by interested and re-sourced actors. I use this concept to I investigate the efforts to introduce mobile technology into health care in England and Finland. I employ a distinct research strategy that avoids a retrospective bias, through the collection and analysis of qualitative data before known outcomes, from a wide range of technology, care, regulatory and intermediary organisations. I uncover some of the difficulties to technology adoption and develop arguments about the types of efforts and the impact of context at the early moment stage that contribute to the further development of the concept of institutional entrepreneurship.